Multiple roles of ventral premotor cortex in BCI task learning and execution - Wander, Jeremiah (Miah); Rao, Rajesh P.N.; Ojemann, Jeffrey (Proceedings of the 6th International Brain-Computer Interface Conference 2014, 2014)
Motor-based brain-computer interface (BCI) use is a learned skill that has been shown to involve multiple cortical areas, though it only explicitly requires modulation of a small area of cortical tissue. The roles being played by these other areas have not yet been determined. In this study, using an electrocorticographic (ECoG) model, we apply a novel computational approach to quantifying the strength and nature of interactions between putative primary motor cortex and ventral premotor cortex (PMv) during BCI use and across BCI skill development. Our findings suggest multiple roles being carried out in PMv that change in strength and nature during skill acquisition.